GLOBALISASI DAN MEDIA KOMUNIKASI SOSIAL: TANTANGAN BAGI PENDIDIKAN ANAK - Don Bosco Karnan Ardijanto (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Media of social communication on the one hand must be seen as a gift of God to be grateful because it has the power to unite, creating and enriching encounter of man and life. But on the other hand must also be recognized that the social communications media not infrequently also used irresponsibly. Globalization and the advancement of social communication media direct and shape society today as a consumer society. Even today's consumer society has become a system of formation and information systems. As a system formation, consumerist society are consciously or unconsciously have formed a personal and behavior, whereas as an information system, consumerist society provides continuous information on the person's consumer society as if it is his identity and becomes his world status. Globalization and social communication media call the parents to respond wisely and responsibly. Parents should accept globalization and social communication media as gifts of God that ought to be thankful for. In addition, parents also develop the right attitude, wise and full responsibility towards globalization and social communication media so that they can still give life and education for children in accordance with the duties and callings of birth and the sacrament of baptism and the sacrament of marriage.